PTH-012 ERCP Training – Achieving Better Outcomes for Patients and Trainees through A New Training Guide. (17th August 2016) - Chinnathurai, BR; Dwyer, L; Saleem, R; Stern, N; Hood, S; Sturgess, R
Abstract : Introduction: It is acknowledged that ERCP is challenging to train both for the trainers and the trainees. Recent evidence has suggested that a much longer period of focused training is required to achieve competence, particularly cannulation of the native ampulla. 1 There is also significant variability in training and performance. Unlike other endoscopic interventions, such as colonoscopy there is a lack of coherent strategy to guide training. The traditional model is unstructured and intuitive, largely conforming to the notion of 'start the trial at the incisors and continue until failure' at which point the trainers take over the scope to complete the procedure. Our model identifies a range of individual skills that can be developed in a structured manner. Methods: Our model in practice, was borne of multiple informal focus groups involving experienced and training ERCPists, both in service and in training courses. Results: Our model of graded progression in ERCP training takes into account the broadly agreed complexity of the each skill set in a deconstructed ERCP.We allocate skills to 4 different domains of increasing complexity, which requires increasing dexterity and cognitive awareness from the endoscopist. In each procedure the trainee would have the opportunity to gain exposure to aspects of ERCP that is appropriate to the stage/level of training, gradually moving along a spectrum of skills of increasing complexity, associated with higher risk of complications. Such a graded progression ensures that the trainee is set up to learn each increasing complex skill with appropriate level of preparedness, enabling smoother progression in training. Trainees are assessed every 10 ERCP for progression. An example of an ERCPist at early stage of training (Pic A) is as shown below. Conclusion: Our training guide could be a component of much needed structure to drive streamlined ERCP training in UK. Adoption of the guide or similar will enable enhanced continuity in training when trainees move between training centres, from initiation to independence. Reference: 1 Verma D, et al . Establishing a true assessment of endoscopic competence in ERCP during training and beyond: a single-operator learning curve for deep biliary cannulation in patients with native papillary anatomy. Gastrointest Endosc . 2007. Disclosure of Interest: None Declared